New records of birds from the Santa Cruz Formation (Early-Middle Miocene) at the Río Santa Cruz Valley, Patagonia, Argentina - Diederle, Juan Marcelo (2019)
The Santa Cruz Formation constitutes one of the most representative units of the late Early Miocene of South America for its abundant and rich fossil record of vertebrates. The diversity of extinct birds is known so far by at least nineteen species grouped in fifteen genera and nine or more families. Most of the avian taxa described from these levels come from localities of the Santa Cruz Province placed next to or along the Atlantic Ocean coast. New materials recovered from the Río Santa Cruz valley, with accurate geographic and stratigraphic provenances, are presented in this contribution. They include rheids, tinamids, and phorusrhacids.